E-COMMERCE AND ANALYSIS OF FACTORS INFLUENCING ITS DEVELOPMENT - Khamraeva Nasimovna, Sayyora (THE INNOVATION ECONOMY, 2025)
The article examines the main economic and social factors influencing the growth of the e-commerce market in Uzbekistan. Economic, social and technological aspects contributing to the growth of the online market based on existing e-commerce facilities in the country were analyzed. The activities of popular trading platforms in Uzbekistan were also analyzed and proposals for their further development were developed.